Adoptees and Americans: Exporting Hans Christian Andersen and Karen Blixen (Isak Dinesen) - Juncker, Clara (American Studies in Scandinavia, 2022)
Hans Christian Andersen and Karen Blixen (aka.) Isak Dinesen have been widely read in America, with Hollywood’s Out of Africa adaptation adding to the attention. Both writers dramatized their alienation with adoption stories reaching across national and racial boundaries. They became iconic writers in the US for many reasons, but their preoccupation with adoption has been insufficiently explored. In fact, their transnational, transracial, transsexual, and cross-species adoption tales have entered US conversations about the Other, since the adoptee arrives in familial structures from “other” ideological, economic, or racial locations. Their adoption tales further fit American rights discourses, by insisting on the rights of belonging and conditions of freedom laid down by reason and law. They also subscribe to emotional discourses that evoke in the audience empathy and emotions related to dignity and humanity. Fairy tale adoptions fit the classic American quest narrative—Huck Finn-style—in which a heroic protagonist takes off into the unknown to find an identity, rooted in liberty, independence, and freedom. In a 21st-century world populated by migrants, refugees, orphans, adoptees, adoptive parents, and adopted or adoptive nations, Andersen and Blixen communicate with global adoption narratives the need for new ideological constellations of family, community, and nation.